Modern language space in the World: tendencies in teaching (Journal of Educational Sciences, 2019)
Kazakhstan is developing in the era of world globalization of the economic sphere and the interna- tionalization of world education. Today in Kazakhstan there is an acute question of the professionals’ language training for various fields of activity. This article is devoted to the consideration of the current state of language space and the situation with learning various languages in the world. This question worried and worries the foreign scientific community and is very relevant. The article discusses the views of scientists, new trends, fashion trends and current trends. The views of modern methodologists and their articles allowed to get acquainted with the issues of concern to the scientific community of the world. Many issues are related to the current state of development of Kazakhstan language education. The article deals with the development of trilingualism and multilingualism, multilingual education and multiculturalism, the leading primacy of the English language and the extinction of the languages of small nations. These problems are the most discussed in the world and are directly related to the sphere of primary, secondary and higher education in our country. The development of trilingualism, the training of literate specialists in three languages, multiculturalism - these are the questions that linguists, method- ologists and teachers of Kazakhstan are working on.Key words: multilingualism, language education, competent specialist, communicative competence, multilingual specialists.